2005
DOI: 10.1002/art.21397
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of cardiovascular risk factors and rheumatoid arthritis clinical manifestations to atherosclerosis

Abstract: Objective. To estimate the contribution of cardiovascular (CV) risk factors and rheumatoid arthritis (RA) disease manifestations to atherosclerosis in RA.Methods. We used high-resolution carotid ultrasound to measure the carotid intima-media thickness (IMT) and plaque in 631 RA patients. Using R 2 measures from multivariable models, we estimated the contribution of demographic characteristics (age, sex, and ethnic group), CV risk factors (diabetes mellitus, hypercholesterolemia, cigarette smoking, hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
144
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(162 citation statements)
references
References 55 publications
14
144
1
3
Order By: Relevance
“…Also notable, the bulb IMT and plaque difference between RA and controls was present only among subjects under 65 years of age. These results are consistent with our finding that RA manifestations contributed more to carotid atherosclerosis in young RA patients 16 , and with Roman and colleagues' finding of a more pronounced difference between RA patients and controls among younger subjects 13 .…”
Section: This Issue Of the Journalsupporting
confidence: 94%
See 1 more Smart Citation
“…Also notable, the bulb IMT and plaque difference between RA and controls was present only among subjects under 65 years of age. These results are consistent with our finding that RA manifestations contributed more to carotid atherosclerosis in young RA patients 16 , and with Roman and colleagues' finding of a more pronounced difference between RA patients and controls among younger subjects 13 .…”
Section: This Issue Of the Journalsupporting
confidence: 94%
“…Thus, it cannot be concluded from them that CV risk factors are not associated with atherosclerosis in RA. In our study of 631 RA patients recruited consecutively, and without specifying CV risk factors as exclusion criteria, we reported that both CV risk factors and inflammation markers were significantly associated with carotid IMT and plaque 16 .…”
Section: Earlier North American Studiesmentioning
confidence: 91%
“…Сочетание РА-специфичных и традицион-ных кардиоваскулярных ФР ассоциируется с наличием атеросклероза в сонных артериях [83], а длительность и ак-тивность заболевания влияют на размер и нестабильность АТБ при РА [84,85].…”
Section: рекомендация 6 скрининг бессимптомных атб с ис-пользованиемunclassified
“…However, dyslipidemia does participate in RA atherogenesis even when the disease is treated with DMARD 18,19 , and its determinants comprise more of the conventional dyslipidemia risk factors than of RA characteristics. The association of dyslipidemia risk factors with lipoproteins further differs markedly by socioeconomic status in RA.…”
Section: Rheumatologymentioning
confidence: 99%